Qualitative Research as a Moral Career. VII Annual Conferenceon Methods in Social Sciences “Sociological Research Methods (A Tribute to Alexander Kryshtanovsky),” September 23−24, 2016, Moscow, Russia - KusimovaTamara (Journal of Economic Sociology, 2016)
The VII Annual Conference on Methods in Social Sciences “Sociological Research Methods (A Tribute to Alexander Kryshtanovsky)” was held from September 23 to 24, 2016, at the National Research University Higher School of Economics in Moscow. The aim of the conference was to highlight the main trends and challenges in methods for collecting and analyzing sociological data, as well as to discuss the most important issues concerning the methodology and methods of acquiring knowledge about modern society. A special section of the conference was devoted to the methodology in qualitative research. Several main issues were discussed, including the validity of qualitative research results, gaining access to gatekeepers and hard-to-find informants, and ethical and moral dilemmas in field research. The keynote speakers of the section were A. Vanke (Institute of Sociology Russian Academy of Science), E. Zdravomyslova (European University at Saint Petersburg), V. Ilin (Saint Petersburg State University), I. Kozlov (St. Tikhon’s Orthodox University, Institute of Sociology Russian Academy of Science), I. Kozina (National Research University Higher School of Economics), Claudio Morrison (Middlesex University, UK), M. Podlesnaya (St. Tikhon’s Orthodox University, Institute of Sociology Russian Academy of Science), M. Semina (Moscow State University), I. Tartakovskaya (IS RAS), A. Temkina (European University at Saint Petersburg), I. Shteinberg (Moscow School of Social and Economic Sciences), and S. Yaroshenko (European University at Saint Petersburg).